Geotechnical Stability Analysis of Soil Displacement: A Case Study of Bridge STA 53, Serang-Panimbang Toll Road, Banten Province - Brillianta Cahya Aryadi; Yudhi Lastiasih; Putu Tantri Kumala Sari (International Journal Labs, 2025)
Serang-Panimbang Toll Road Project is Project National Strategic Project (PSN) in Indonesia which is the development of Economic Zones Special (KEK) Tourism Cape Lesung. STA 53 Bridge on the Serang-Panimbang Toll Road Project face challenge stability slope consequence condition complex geotechnical engineering, in particular existence claystone formation problematic (Formation Bojong). Research This analyze causes and mechanisms shift land on site the through approach integrated. Investigation layer soil and instrumentation data field used For obtain material parameters. Analysis back -analysis with method element until (FEM) then implemented For engineer repeat failure. FEM results were validated with resistivity data from survey geoelectricity For confirm types and triggers movement land. Allegedly also reinforced with depth data shift the ground as read by the inclinometer, strengthens suspicion Where condition layer vulnerable land to weakening due to water. Study This succeed identify factor controller instability and provide key parameter recommendations For planning reinforcement slope as well as ensure security structure bridge.